The C0-C2 axial rotation test: normal values, intra- and inter-rater reliability and correlation with the flexion rotation test in normal subjects - Satpute, K.; Nalband, S.; Hall, Toby (Maney Publishing, 2018)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. Objectives: Impairment in upper cervical spine mobility is associated with cervicogenic headache severity and disability. Measures of such mobility include the flexion-rotation test (FRT), which requires full cervical flexion and may be influenced by lower cervical spine dysfunction. The C0-C2 axial rotation test also evaluates upper cervical mobility but normal values and reliability have not been reported. Our objective is to determine normal values, and intra-rater and inter-rater reliability of the C0-C2 axial rotation test. Methods: Two therapists independently evaluated the FRT and C0-C2 axial rotation test with an iPhone compass application on 32 asymptomatic subjects with mean age 40.53 (SD 11.64) years on two occasions. Measurement procedures were standardized; and order of testing randomized. Results: For the FRT and C0-C2 axial rotation test reliability was high (ICC > 0.88). For rater one, Mean range to the left during the FRT and C0-C2 axial rotation test was 45.0° (6.04) and 14.43° (2.94), respectively, while range to the right was 44.6° (6.57) and 15.44° (2.68). For the FRT and C0-C2 axial rotation test the standard error of measurement was at most 2°, while the minimum detectable change was at most 4°. A strong positive correlation exists between the FRT and C0-C2 axial rotation test (r = 0.84, P < 0.01). Discussion: The range recorded during the C0-C2 axial rotation test and FRT have high levels of reliability when evaluated using an iPhone. The strong correlation between the FRT and C0-C2 axial rotation test indicate that both may be measuring similar constructs, but each test needs to be referenced to normal values.